Students Difficulties in Using Simple Past Tense in Narrative Text at Tenth Grade of Senior High School 8 Muaro Jambi - Suyadi, Suyadi; Silfia, Efa; Nurhasanah, Riska Meilina (JELT: Journal of English Language Teaching, 2024)
This research aims to find out the levels of difficulty faced by tenth-grade students at Senior High School 8 Muaro Jambi in using simple past tense within narrative texts. The research used a quantitative descriptive research design with purposive sampling. 28 students from class XE 4 were taken as participants. The researcher used a test as an instrument. The findings reveal that the students fall into 4 categories: Very Poor, Poor, Moderate, and Good levels. 13 students in the "Very Poor" level, and 10 students in the “Poor” level. It indicates difficulties in using simple past tense. Students performed better in answering Regular verb questions than Irregular ones. The mean score that obtained is 26.43. The standard deviation is 18.72, indicating a relatively high degree of variability. The highest score obtained is 62.5, the lowest is 0. The spread of scores suggests a wide range of individual differences, suggesting heterogeneity in performance within the sample.Keywords: Level of difficulty, narrative text, simple past tense